Membentuk Karakter Mahasiswa Unggul, Kritis dan Responsif Melalui Metodologi Penelitian - Ade Putra Ode Amane; Kisman Karinda; Haminun Dg. Matorang; La Ode Sabirila Jayalangi; Shela Divana Dewi; Hasrul Lambudi; Sri Ayu Laali; Filo Leonardo Tinggogoy (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
Community service activities carried out by lecturers and students through collaboration in Basic Leadership Training aim to shape the character of new students of the Government and Communication Science Study Program, Faculty of Social and Political Sciences, Muhammadiyah University of Luwuk, who are superior, critical, and responsive. This activity introduces the Open Journal System (OJS) and the Mendeley application as a means to improve students' abilities in writing scientific papers. With a comprehensive research methodology approach, students are guided to get to know and practice scientific writing more effectively. The results of this activity show that students not only gain technical skills in writing, but also develop in aspects of leadership and critical thinking on local, national, and international issues. This program has succeeded in providing a strong foundation for students' academic and character development, preparing them to become competent and insightful leaders.